Monte Carlo simulation of gamma-ray total counting efficiency for a Phoswich detector - Gurler, Orhan; Gundogdu, O.; Kaynak, G.; Yalcin, S. (Elsevier BV, 2009)
The LB 1000-PW detector is mainly used for determining total alpha, beta and gamma activity of low activity natural sources such as water, soil, air filters and any other environmental sources. Detector efficiency needs to be known in order to measure the absolute activity of such samples. This paper presents results on the total gamma counting efficiency of a Phoswich detector from point and disk sources. The directions of photons emitted from the source were determined by Monte Carlo techniques and the true path lengths in the detector were determined by analytical equations depending on photon directions. Results are tabulated for various gamma energies.